The Meaningfulness of Life Among Parents Who Adopt Children with Autism: A Qualitative Psychological Perspective - Hannah Fadzila Saragih; Fitrania Maghfiroh (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2026)
Adopting a child with autism presents unique psychological, emotional, and social challenges that differ significantly from those experienced by biological parents. In Indonesia, adoption involving children with autism remains relatively uncommon, and empirical studies examining the lived experiences of adoptive parents are still limited. Most existing research has focused on parental stress, coping strategies, and caregiving burdens, with little attention given to how adoptive parents construct and experience meaning in life through their parenting roles. This study aimed to explore the meaning of life among adoptive parents of children with autism by examining their subjective experiences and meaning-making processes. This research employed a qualitative case-study design. Participants consisted of a married couple who adopted a child diagnosed with autism through kinship-based adoption. Data were collected through semi-structured interviews, non-participant observations, and triangulation with a significant other. The data were analyzed thematically to identify patterns related to meaning construction, emotional experiences, and parental roles. The findings indicate that adoptive parents construct meaning in life through acceptance, commitment, emotional resilience, and spiritual reflection in responding to parenting challenges. Parenting a child with autism becomes a source of personal growth and life purpose, despite ongoing emotional and practical demands. This study contributes to meaning-in-life literature by highlighting the distinctive experiences of adoptive parents and offers practical implications for psychological support and family-based interventions.